Structure and composition of ichthyofauna associated with cage fish farming and compared to a control area after severe drought in a Neotropical reservoir - Orlandi-Neto, Aymar [UNESP]; Amorim, Rafael Vieira [UNESP]; Delariva, Rosilene Luciana; Camargo, Antonio Fernando Monteiro [UNESP]; Veríssimo-Silveira, Rosicleire [UNESP]; Ramos, Igor Paiva [UNESP] (FapUNIFESP (SciELO), 2022)
In 2014, an atypical drought in Southeast Brazil drastically reduced the water level in several reservoirs. We investigated the effects of this drought and the subsequent flood period on the attributes of ichthyofauna in an aquaculture and in a control area. Fish were collected bimonthly between 2014 and 2015 (drought) and 2016 (wet), using gill nets in the two sample areas in the Ilha Solteira reservoir, Upper Paraná River basin, Brazil. We compared ichthyofauna attributes between the drought and wet seasons in each area and between areas within each season. In the aquaculture area, the assemblages showed similar characteristics between the seasons. By contrast, the control area varied between seasons, with greater species richness, Shannon diversity, species evenness, and less β diversity in the wet season. Comparisons between areas in each season showed higher abundance in the fish farm within the drought season. Changes in structure and composition in the control area are possibly associated with new areas and resources made available by the flooding of marginal areas during the wet season. We inferred that the effect of the flood on the aquaculture community was attenuated by the continuous habitat structure such as shelters and food provided by the enterprise.
Keywords: Diversity; Ilha Solteira reservoir; Invasive species; Upper Paraná River; Water crisis